2018
DOI: 10.1371/journal.pone.0198906
|View full text |Cite
|
Sign up to set email alerts
|

Immune response to recombinant Burkholderia pseudomallei FliC

Abstract: Burkholderia pseudomallei is a flagellated Gram-negative bacterium which is the causative agent of melioidosis. The disease poses a major public health problem in tropical regions and diabetes is a major risk factor. The high mortality rate of melioidosis is associated with severe sepsis which involves the overwhelming production of pro-inflammatory cytokines. Bacterial flagellar protein (flagellin) activates Toll-like receptor 5 (TLR5)-mediated innate immune signaling pathways and induces adaptive immune resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…RT-qPCR analysis of DEGs included in inflammatory response, such as IL1A, IL6, TNFAIP3, NFκB2, and GKN2 ( Figure 5), was therefore conducted. B. pseudomallei increased the mRNA expression of TNFAIP3 and IL-6 in human lung epithelial cell, which was consistent with the current research that proinflammatory mediators of TNF-α and IL-6 increased in the liver of mice following infection with B. pseudomallei and in serum samples of melioidosis patients (Ulett et al, 2000;Koosakulnirand et al, 2018). Activated UPR transcription factors can induce inflammatory response, which play an important role in the pathogenesis of inflammation (Bettigole and Glimcher, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…RT-qPCR analysis of DEGs included in inflammatory response, such as IL1A, IL6, TNFAIP3, NFκB2, and GKN2 ( Figure 5), was therefore conducted. B. pseudomallei increased the mRNA expression of TNFAIP3 and IL-6 in human lung epithelial cell, which was consistent with the current research that proinflammatory mediators of TNF-α and IL-6 increased in the liver of mice following infection with B. pseudomallei and in serum samples of melioidosis patients (Ulett et al, 2000;Koosakulnirand et al, 2018). Activated UPR transcription factors can induce inflammatory response, which play an important role in the pathogenesis of inflammation (Bettigole and Glimcher, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…In general, innate immune mechanisms are critical in determining the outcome of infections caused by bacterial pathogens. Recent studies have reported that B. pseudomallei increased the production of inflammatory cytokines such as TNF-α, IL-1β and IL-6 in vivo in serum samples of melioidosis patients [28]. Proinflammatory cytokine mRNA of TNF-α, IL-1β and IL-6 increased in the liver of mice following infected with B. pseudomallei [29].…”
Section: Discussionmentioning
confidence: 98%
“…PART 1 from human melioidosis patients as well as animal studies has greatly facilitated the selection of target antigens and rational design of candidate vaccines [33][34][35][36][37][38][39][40][41][42][43]. The identification of immunoreactive B and T cell antigens VACCINES FOR EMERGING PATHOGENS: FROM RESEARCH TO THE CLINIC.…”
Section: Multi-component Vaccinesmentioning
confidence: 99%
“…The identification of immunoreactive B and T cell antigens VACCINES FOR EMERGING PATHOGENS: FROM RESEARCH TO THE CLINIC. PART 1 from human melioidosis patients as well as animal studies has greatly facilitated the selection of target antigens and rational design of candidate vaccines [33][34][35][36][37][38][39][40][41][42][43]. Certain bacterial antigens, such as capsule polysaccharide (CPS), FliC, BopE, AhpC and many outer membrane proteins (Omp), are routinely recognized as highly reactive with patient immune sera or peripheral blood mononuclear cells (PBMCs), and many of these antigens confer partial protection when used as individual subunit vaccines [7].…”
Section: Multi-component Vaccinesmentioning
confidence: 99%